EMPOWERMENT OF DIABETES MELLITUS PATIENT DURING COVID-19 PANDEMIC ERA THROUGH ONLINE GATHERING - Nur Rochmah; Sukmawati Basuki; Fatimah Arief; Muhammad Faizi; Faisal Faisal; Juniastuti Juniastuti; Herman Kosasih (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2022)
Introduction: In the COVID-19 pandemic, social restriction and lock-down policies were implemented. It has far-reaching implications in many sectors of life including health, particularly in patients with chronic diseases, one of which is Type-1 Diabetes Mellitus (T1DM). The purpose of this community service in the form of online gathering is to facilitate patients to ask questions and consult with pediatricians, due to the limitations of patients to consult directly due to the pandemic. Methods: Community service is conducted online for T1DM patients or their relatives on Sunday, September 26, 2021, from 12.00 - 13.30 WIB. The Community service was divided into several stages, including before, during, and after the online gathering.Â  The T1DM patients or their relatives are participants in this community services. The topic are types of Diabetes Mellitus, clinical presentation, disease progression, the diagnostic process, and its management therapy of type 1 diabetes mellitus. Results: The community service was attended by 54 parents of T1DM patient. The online gathering goes smoothly, without being constrained by something. During the online gathering, subjects actively participate in every session during the online gathering. Several questions were asked by the participants and answered well by the speakers. Conclusion: This community services activities allow participant to be able to ask question about their problem according to diabetes mellitus. Participants can consult online with pediatricians. This online gathering has a limited time, so participants can be divided into several breakout rooms with several accompanying pediatricians, so that the QnA session can be done optimally.